Dekonstruksi Makna Datun Kendau pada Masyarakat Kenyah di Desa Budaya Pampang - Lenjau, Septiana; Putra, Bayu Arsiadhi; Setyoko, Aris (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
In the Kenyah community in the Pampang Cultural Village, Datun Kendau has undergone many changes, which are more likely to add Sampe and change the lyrics of the song to the Kenyah language commonly used in Pampang Village. This study aims to describe the form and meaning of Datun Kendau in the Kenyah community in Pampang Cultural Village. This research uses qualitative methods with observation techniques, data collection techniques and data analysis. The observation technique includes the object of study and the determination of informants. Data collection techniques include literature study, interviews, and documentation. Finally, data analysis techniques using field data. The results show that the Datun Kendau show's form has changed, which consists of a simple musical structure and consists of repeated melodic motifs. Datun Kendau has adapted to the activities of tourism events and young Kenyah artists' interests in Pampang Village. The creation of the reality of the meaning of Datun Kendau is interpreted as a way of adaptation, the formality of performances, and activities that are profitable and occur because of broken communication between the older generation and the younger generation